Особливості інтегративного підходу до загальноосвітньої та загальнотехнічної підготовки майбутніх фахівців будівельного профілю у ПТНЗ - Козловська, Ірина; Білик, Оксана (Видавництво Львівської політехніки, 2013)
В статье обосновано концептуальные положения интегративного подхода к общетехнической и общеобразовательной подготовке будущих специалистов строительного профиля в профессионально-технических учебных заведениях. Выявлены практического применения интегративного подхода к изучению курса материаловедения на основе теории строительных материалов и физики на интегративной основе. The article grounds conceptual statements of integrative approach to general educational and general technical training of future specialists of building profile in vocational educational establishments. The authors educe possibilities of practical application of integrative approach to the study of the course of material science basing on the theory of construction materials and physics on the integrative principles.
Особенности интегративного подхода к общеобразовательной и общетехнической подготовке будущих специалистов строительного профиля в ПТУЗ
Peculiarities of integrative approach to general educational and general technical training of future specialists of building profile in vocational educational establishments
Keywords: интегративный подход; профессионально-техническое учебное заведение; общеобразовательные дисциплины; общетехнические дисциплины; физика; материаловедение; integrative approach; vocational educational establishment; general subjects; general technical subjects; physics; material science